Hubungan Preferensi Pembayaran dan Impulsive Buying pada Dewasa Awal Pengguna E-commerce di Bukittinggi - Aliyan Syarif Mukhtar; Yolivia Irna Aviani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
This study aims to determine the relationship between payment preferences and impulsive buying behavior among young adult e-commerce users in Bukittinggi. Digital payment methods are suspected to influence impulsive buying tendencies by reducing financial awareness. This study used a quantitative approach involving 93 young adult respondents (18-40 years old) who actively shop online. sampling technique used in this study was incidental sampling, data were collected through questionnaires measuring aspects of payment preferences (such as positive emotion cash, positive emotion card, social gratification, and money management) and impulsive buying (cognitive and affective aspects). Validity and reliability tests confirmed that the research instrument met the established criteria. Data analysis using the Pearson Product Moment correlation test showed a very low and non- significant positive relationship between payment preferences and impulsive buying (r = -0.047, p = 0.656). Although statistically insignificant, the variable description indicates that respondents tended to have a high level of impulsive buying, with payment preferences dominated by social considerations (social gratification). These findings imply the importance of enhancing digital financial literacy and expenditure management for consumers, as well as considering local socio-cultural factors in understanding consumer behavior.